Comparative effectiveness of antiarrhythmic drugs for rhythm control of atrial fibrillation. Issue 5 (May 2016) - Qin, Dingxin; Leef, George; Alam, Mian Bilal; Rattan, Rohit; Munir, Mohamad Bilal; Patel, Divyang; Khattak, Furqan; Adelstein, Evan; Jain, Sandeep K.; Saba, Samir
Abstract: Introduction: Although there are many different antiarrhythmic drugs (AADs) approved for rhythm management of atrial fibrillation (AF), little comparative effectiveness data exist to guide drug selection. Methods: We followed 5952 consecutive AF patients who were prescribed amiodarone ( N  = 2266), dronedarone ( N  = 488), dofetilide ( N  = 539), sotalol ( N  = 1718), or class 1C agents ( N  = 941) to the primary end point of AF recurrence. Results: Median follow-up time was 18.2 months (range 0.1–101.6 months). Patients who were prescribed amiodarone had the highest, while patients on class 1C agents had the lowest baseline CHA2 DS2 -VASc score, Charlson comorbidity index, and burden of comorbid illnesses including coronary artery disease, congestive heart failure, diabetes mellitus, hyperlipidemia, chronic obstructive lung disease, chronic kidney disease, or cancer ( p  < 0.05 for all comparisons). After adjusting for baseline characteristics, using dronedarone as benchmark, amiodarone [hazard ratio (HR) 0.58, p  < 0.001], class 1C agents (HR 0.70, p  < 0.001), and sotalol (HR 0.79, p  = 0.008), but not dofetilide (HR 0.87, p  = 0.178) were associated with less AF recurrence. In addition, compared to dronedarone, amiodarone and class 1C agents were associated with lower rates of admissions for AF (HR 0.55, p  < 0.001 for amiodarone; HR 0.71, p  = 0.021 for class 1C agents) and all-cause mortality was lowest in patients treated with class 1C agents (HR 0.42, p  = 0.018). The risk of stroke was similar among all groups. Conclusion: Compared with dronedarone, amiodarone, class 1C agents, and sotalol are more effective for rhythm control, while dofetilide had similar efficacy. These findings have important implications for clinical practice.